2018
DOI: 10.1002/ctpp.201700138
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of nitrogen doping on the carbon nanofiber growth via catalytic plasma‐enhanced chemical vapour deposition process

Abstract: An analytical model is developed to describe the effects of nitrogen doping on the growth of the carbon nanofibers (CNFs) and to elucidate the growth mechanism of nitrogen‐contained carbon nanofibers (N‐CNFs) on the catalyst substrate surface through the plasma‐enhanced chemical vapour deposition (PECVD) process. The analytical model accounts for the charging of CNFs, kinetics of all plasma species (electrons, ions, and neutrals) in the reactive plasma, generation of carbon species on the catalyst nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The introduction of oxygen-containing functionalities has been demonstrated in carbon nanofibers, and their effect on their activity as catalyst or as catalyst support has been tested in several reactions, including ozonation [24] and catalytic wet air oxidation [25] of water contaminants, in fuel cell electrodes [26,27], nitrate [28], nitrobenzene [29,30], naphthalene [31], cinnamaldehyde [32,33], phenylacetylene [34] hydrogenation, nitrous oxide reduction [35], electrocatalytic oxygen reduction [35], methanol oxidation [36], Fischer-Tropsch reaction [27], and others [5]. Similar studies have been carried out when using other elements as dopants, such as nitrogen [37][38][39][40][41][42][43][44][45][46][47], boron [38,45,48], potassium [27,38,49], fluorine [50,51], phosphorous [45], or sulfur [52][53][54]. Nevertheless, the various morphologies of the 1D carbon nanofibers illustrated in Figure 2 may offer particular characteristics of interest to specific catalytic applications, in particular the potential presence of a large number of defects on the carbon lattice of the carbon nanofibers when compared with carbon nanotubes (Figure…”
Section: Carbon Nanofibers In Catalysismentioning
confidence: 99%
“…The introduction of oxygen-containing functionalities has been demonstrated in carbon nanofibers, and their effect on their activity as catalyst or as catalyst support has been tested in several reactions, including ozonation [24] and catalytic wet air oxidation [25] of water contaminants, in fuel cell electrodes [26,27], nitrate [28], nitrobenzene [29,30], naphthalene [31], cinnamaldehyde [32,33], phenylacetylene [34] hydrogenation, nitrous oxide reduction [35], electrocatalytic oxygen reduction [35], methanol oxidation [36], Fischer-Tropsch reaction [27], and others [5]. Similar studies have been carried out when using other elements as dopants, such as nitrogen [37][38][39][40][41][42][43][44][45][46][47], boron [38,45,48], potassium [27,38,49], fluorine [50,51], phosphorous [45], or sulfur [52][53][54]. Nevertheless, the various morphologies of the 1D carbon nanofibers illustrated in Figure 2 may offer particular characteristics of interest to specific catalytic applications, in particular the potential presence of a large number of defects on the carbon lattice of the carbon nanofibers when compared with carbon nanotubes (Figure…”
Section: Carbon Nanofibers In Catalysismentioning
confidence: 99%
“…This method is performed at a lower temperature than the normal CVD method. The collision of a gas-phase molecule with electrons facilitates the gas molecules’ decomposition, excitation, compounding, and ionization, thereby producing high-activity chemical groups. Saidin et al synthesized CNFs utilizing the plasma-enhanced CVD (PECVD) method by employing a Ni/Cr-glass thin film catalyst for CNF growth. The influence of the different thicknesses of catalyst and acetylene to gaseous ammonia ratios were investigated, and they concluded that the optimum condition for the synthesis of CNFs is a 1:3 acetylene to NH 3 gas ratio with the width of 15 nm for the Ni/Cr-catalyst.…”
Section: Synthesis Of Carbon Nanofibersmentioning
confidence: 99%
“…Shoukat and Khan synthesized vertically aligned CNFs by inductively coupled plasma-enhanced CVD using a temperature of ∼650 °C and toluene as a carbon source. Gupta and Sharma studied the effect of N doping on CNF growth by plasma-enhanced CVD and determined that N-doped CNFs had a lower tip diameter, smaller height, and improved field emission characteristics compared to undoped CNFs. Low substrate temperature and high deposition rates are required in this method …”
Section: Synthesis Of Carbon Nanofibersmentioning
confidence: 99%
“…The plasma contains a large amount of high-energy electrons that can provide the activation energy required for the chemical vapor deposition process. The collision of electrons with gas phase molecules can promote the decomposition, compounding, excitation, and ionization processes of gas molecules, and generate various chemical groups with high activity [35,36,37]. While the plasma enhanced chemical vapor deposition method can produce aligned CNFs, the cost of this method is high, the production efficiency is low, and the process is difficult to control.…”
Section: Synthesis Of Carbon Nanofibers (Cnfs)mentioning
confidence: 99%